2019
DOI: 10.1002/hec.3854
|View full text |Cite
|
Sign up to set email alerts
|

The effects of e‐cigarette minimum legal sale age laws on youth substance use

Abstract: We use difference-in-differences models and individual-level data from the national and state Youth Risk Behavior Surveillance System from 2005 to 2015 to examine the effects of e-cigarette minimum legal sale age (MLSA) laws on youth cigarette smoking, alcohol consumption, and marijuana use. Our results suggest that these laws increased youth smoking participation by about one percentage point and approximately half of the increased smoking participation could be attributed to smoking initiation. We find littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Our best estimate of a 0.6 pp increase in smoking in a given trimester among rural teens is slightly smaller than previous estimates for teens generally (not specifically rural, nor pregnant) from cross-sectional difference-in-differences models. Three other studies found that ENDS MLSAs increased teen smoking by approximately 0.8 to 1.0 pp (Dave et al, 2019;Friedman, 2015;Pesko et al, 2016), while a fourth study used Monitoring the Future data to find that ENDS MLSAs decreased high school senior smoking participation by 2.0 pp (Abouk & Adams, 2017). One reason that our estimate may be smaller than those in the first three studies is that our results are for a subset of women rather than for both men and women, and women generally have lower tobacco use rates than men.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our best estimate of a 0.6 pp increase in smoking in a given trimester among rural teens is slightly smaller than previous estimates for teens generally (not specifically rural, nor pregnant) from cross-sectional difference-in-differences models. Three other studies found that ENDS MLSAs increased teen smoking by approximately 0.8 to 1.0 pp (Dave et al, 2019;Friedman, 2015;Pesko et al, 2016), while a fourth study used Monitoring the Future data to find that ENDS MLSAs decreased high school senior smoking participation by 2.0 pp (Abouk & Adams, 2017). One reason that our estimate may be smaller than those in the first three studies is that our results are for a subset of women rather than for both men and women, and women generally have lower tobacco use rates than men.…”
Section: Discussionmentioning
confidence: 92%
“…Four studies have explored this question using cross-sectional two-way fixed effects models, and there is some disagreement among the estimates. Three of these studies found that ENDS MLSAs increased teen smoking by approximately 0.8 to 1.0 pp (Dave, Feng, & Pesko, 2019;Friedman, 2015;Pesko, Hughes, & Faisal, 2016), while a fourth study used Monitoring the Future data and found that ENDS MLSAs decreased smoking participation of high school seniors by 2.0 pp (Abouk & Adams, 2017). At least one other study suggests that ENDS are complements with cigarettes, although within a sample of primarily adult cigarette smokers (Cotti, Nesson, & Tefft, 2018).…”
Section: Department Ofmentioning
confidence: 99%
“…For example, Friedman (2015) uses the National Survey on Drug Use and Health and finds that states implementing restrictions on youth access to e-cigarettes see increases in youth past 30 day smoking rates, suggesting that e-cigarettes and traditional cigarettes are substitutes among adolescents. Similarly, Pesko, Hughes, and Faisal (2016) and Dave, Feng, and Pesko (2019) use the Youth Risk Behavior Surveillance System data and restrictions on adolescent access to ecigarettes, finding evidence that the two products are substitutes for this population. Pesko and Currie (2019) have comparable findings for pregnant adolescents using birth record data.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…An MLSA increases the non-pecuniary (or hassle) cost of e-cigarettes as youth below the MLSA are prohibited from legally purchasing the product. Friedman (2015); Pesko, Hughes, and Faisal (2016); and Dave, Feng, and Pesko (2019) show evidence of substitution: following the passage 4 Several studies use price variation (without instrumentation) to document that e-cigarette purchases fall as ecigarette prices rise (Stoklosa, Drope, and Chaloupka 2016, Pesko and Warman 2017, Zheng et al 2017, Marti et al 2019. A number of studies additionally use market-level price variation to study cross-price elasticities of demand, without a consensus reached on whether the products are economic substitutes or complements (Huang et al 2018, Stoklosa, Drope, and Chaloupka 2016, Pesko and Warman 2017, Zheng et al 2017.…”
Section: Background and Related Literaturementioning
confidence: 99%